170k views
3 votes
Let f(x) = x^2-6 and g(x) =10x . Find (g ° f)(x)

User Asn
by
5.0k points

2 Answers

2 votes

Answer:

10x^2-60

Explanation:

(G o F)(x) is the same as g(f(x)). We know that f(x)=x^2-6. So now you have to find g(x^2-6). To solve for that plug in x^2-6 in for x in the original equation for g(x). You get 10(x^2-6) or 10x^2-60

User Chirag Vidani
by
5.4k points
7 votes

Answer:


(g \circ f)(x)=10x^2-60

Answer:
10x^2-60

Explanation:


(g \circ f)(x)=g(f(x))

Replace
f(x) with
x^2-6.

This gives us:


(g \circ f)(x)=g(f(x))


(g \circ f)(x)=g(x^2-6)

This means to replace the old input variable with new input,
(x^2-6).

Let's do that:


(g \circ f)(x)=10(x^2-6)

They probably want you to distribute:


(g \circ f)(x)=10x^2-60

User BAK
by
4.2k points